Canakinumab in the treatment of systemic juvenile idiopathic arthritis: a retrospective single center study in China - Xiaona Zhu; Ruohang Weng; Yanyan Huang; Yongbin Xu; Jun Yang; Tingyan He (Frontiers Media S.A., 2024)
ObjectiveSystemic juvenile idiopathic arthritis (sJIA) is characterized by excessive production of proinflammatory cytokines. As an anti-IL-1 agent, canakinumab has been approved in the USA and Europe for the treatment of sJIA patients aged ≥2 years. However, the use of canakinumab has never been reported in China. In this study, we aimed to assess the efficacy and safety of canakinumab in Chinese patients with sJIA.MethodsA total of 11 patients with sJIA who were treated with canakinumab were included in this study. Clinical data were collected retrospectively from medical records. Efficacy was evaluated by the systemic juvenile arthritis disease activity score (sJADAS). The follow-up was performed at canakinumab initiation, at months 1, 3, 6, 9 and 12, or at the last follow-up.ResultsOf the 11 patients enrolled, 91.0% (10/11) had previously received treatment with tocilizumab. The mean duration of canakinumab was 9 (3-18) months. 45.5% (5/11) of patients showed complete response, 45.5% (5/11) showed partial response, and 9.0% (1/11) showed no response. 18.2% (2/11) experienced disease flare during the treatment with canakinumab. 81.8% (9/11) of patients successfully reduced the dose of corticosteroids, with six discontinuing corticosteroids. 45.6% (5/11) of patients experienced infection. No serious adverse events occurred during the treatment with canakinumab.ConclusionsCanakinumab may be effective and tolerable for Chinese sJIA patients, helping to reduce the dosage of corticosteroids. However, additional researches on large samples are required to evaluate its efficacy and safety.